Philippine schools librarianship a primer for teacher-librarians - Orendain, Maria Arcilla (Rex Book Store, 1991)
This book aims to become students and teachers' necessary reading material that would prepare them in the performance of their dual role to teach and give library services. This book describes and explains the Filipino Teacher-librarian profession. It contains a guide to teaching programs for Instructional libraries as well as non-instructional libraries.